Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/14786419.2016.1154057
|View full text |Cite
|
Sign up to set email alerts
|

Anti-melanoma and UV-B protective effect of microbial pigment produced by marine Pseudomonas aeruginosa GS-33

Abstract: Bioactivity of a microbial pigment, extracted from fermented broth of culture marine Pseudomonas aeruginosa was screened for anticancer activity against human skin melanoma cell line SK-MEL-2. Upon characterisation, the pigment was confirmed as Phenazine-1-carboxylic acid (PCA). The PCA was found effective against SK-MEL-2 cell line at low concentration (GI50 value <10 μg/mL). Reduced cell density and cell shrinkage with typical morphological changes such as rounding of cells with loss/breaking of cell membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Phenazine-1-carboxylic acid (PCA) has been produced, purified and characterized by the marine bacterium Pseudomonas aeruginosa GS-33 [ 19 ]. This compound showed a potent dose-dependent anticancer activity on SK-MEL-2 melanoma cells with a GI 50 (growth inhibition of 50%) of 2.30 μg/mL (since a GI 50 value of 10 μg/mL is considered to demonstrate anticancer activity in the case of pure compounds [ 20 ]).…”
Section: Marine Microorganismsmentioning
confidence: 99%
“…Phenazine-1-carboxylic acid (PCA) has been produced, purified and characterized by the marine bacterium Pseudomonas aeruginosa GS-33 [ 19 ]. This compound showed a potent dose-dependent anticancer activity on SK-MEL-2 melanoma cells with a GI 50 (growth inhibition of 50%) of 2.30 μg/mL (since a GI 50 value of 10 μg/mL is considered to demonstrate anticancer activity in the case of pure compounds [ 20 ]).…”
Section: Marine Microorganismsmentioning
confidence: 99%
“…Shanmugapriya et al (2019) [45] and Patil et al ( 2016) [46] demonstrated the efficacy of ASX not only in inhibiting ROS but also in inhibiting certain cancer cells. Skin pre-treatment with AT caused only poor cell viability compared to pretreatment with ASX-T, ASX-O and CRO at the same concentration (4 μM).…”
Section: Viability Of Cells From Skin Explants Pre-treated With the T...mentioning
confidence: 99%
“…PCA (Phenazine -1-carboxylic acid) pigment extracted from marine P. aeruginosa sp. GS-33 correspondingly showed inhibition against SK-MEL-2 (human skin melanoma cell line) [105]. Another pigment violacein extracted from Antarctic bacterium isolate, identified as a member of the genus Janthinobacterium (named as Janthinobacterium sp.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Considering the cosmetic market value worldwide, researchers have also made efforts to explore the use of marine-derived bpBPs in skincare products. The addition of the pigment PCA in a solution of commercial sunscreen enhanced its UV-B (ultraviolet B-rays) protection and increased the SPF (sun protection factor) values up to 10% to 30% [105].…”
Section: Use In Cosmeticsmentioning
confidence: 99%